Nilai Nilai Pendidikan Dalam Kitab Fawaidhul Mukhtarah dan Aplikasinya Untuk Meningkatkan Disiplin Santri Ponpes Darullughah Wadda’wah - Ismail Alatas (Program Studi Bimbingan dan Konseling Islam, 2022)
The Book of Fawaidhul Mukhtarah is one of the moral books which contains advice about the deeds of a human being which is complemented by interpretations of the Al-Quran and Hadith. The research that the author did was field research, namely explaining and describing conditions and phenomena that were clearer about the situation that occurred. Discipline values in the book that can increase the discipline of Dalwa students are: a) Discipline in Worship. Among the results of the discipline produced from the book Fawaidhul Mukhtarah is the discipline of prayer. As students of the Darullughah Wadda'wah Islamic Boarding School, they must pray the five daily prayers on time. b) Social Discipline. A Dalwa santri must have social discipline, namely a mental attitude of the santri who has obedience or adherence to the rules and regulations of the Islamic boarding school. This social discipline is reflected in the attitudes and behavior of the santri who always live in an orderly, obedient and obedient manner towards the norms of the santri, such as being orderly in carrying out worship at the mosque, when using Islamic boarding school's belongings, and when holding meetings in commemoration of religious activities and holidays. national level, as well as in associating and working together. With the enactment of discipline, social life will become orderly and orderly and mutual progress will be realized